Swift/XRT–NuSTAR spectra of type 1 AGN: confirming INTEGRAL results on the high-energy cut-off. Issue 2 (15th January 2019) - Molina, M; Malizia, A; Bassani, L; Ursini, F; Bazzano, A; Ubertini, P
Abstract: We present the 0.5–78 keV spectral analysis of 18 broad-line AGN belonging to the INTEGRAL complete sample. Using simultaneous Swift -XRT and NuSTAR observations and employing a simple phenomenological model to fit the data, we measure with a good constraint the high-energy cut-off in 13 sources, while we place lower limits on five objects. We found a mean high-energy cut-off of 111 keV (σ = 45 keV) for the whole sample, in perfect agreement with what found in our previous work using non-simultaneous observations and with what recently published using NuSTAR data. This work suggests that simultaneity of the observations in the soft and hard X-ray band is important but not always essential, especially if flux and spectral variability are properly accounted for. A lesser agreement is found when we compare our cut-off measurements with the ones obtained by Ricci et al. (2017 ) using Swift -BAT high-energy data, finding that their values are systematically higher than ours. We have investigated whether a linear correlation exists between photon index and the cut-off and found a weak one, probably to be ascribed to the non-perfect modelling of the soft part of the spectra, due to the poor statistical quality of the 2–10 keV X-ray data. No correlation is also found between the Eddington ratio and the cut-off, suggesting that only using high statistical quality broad-band spectra is it possible to verify the theoretical predictions and study the physical characteristics of the hot corona and its geometry.